A study on factors that affect research productivity among lecturers servicing at International Education Center (INTEC) / Noorkhaida Abdul Murad, Rosma Mohd Dom and Zalina Zahid - Abdul Murad, Noorkhaida; Mohd Dom, Rosma; Zahid, Zalina (2002)
Research is important for the progress of a university. Excellence in research can lead to innovation and can benefit society, industries and nation. Despite its importance, research productivity is still below the expected target. From 1985 until 1999, only 3% of the total number of academic staff of UiTM were involved in research activities. (Prof Datuk Ibrahim Abu Shah, 2000). Thus, the objective of this study are to: (i) determine the level of research productivity among INTEC lecturers (ii) identify the factors which affect research productivity (iii) identify Special Interest Groups among INTEC lecturers. A questionnaire is distributed among 50 lecturers servicing at INTEC. The responses were analysed using SPSS.